Competition and trust: Evidence from German car manufacturers - Leonardo Felli; Johannes Koenen; Konrad O. Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We explore the determinants and effects of trust relationships between upstream suppliers and downstream producers. Using unique survey data on individual supplier-buyer relationships in the German automotive industry, we show, by means of different measures of supplier-buyer trust, that higher levels of trust mitigate relationship-specific underinvestment in a classical hold-up situation. Moreover, contrary to the extant literature, we show that higher levels of supplier's trust are reflected in the buyer's choice of a more competitive procurement strategy among potential suppliers.
Keywords: D86; D22; L22; L62; 330; trust; hold-up problem; competition; specific investment; suppliers; car manufacturers; German automotive industry; Kraftfahrzeugindustrie; Kraftfahrzeugzulieferer; Lieferanten-Kunden-Beziehung; Vertrauen; Sunk Costs; Wettbewerb; Beschaffungsplanung; Deutschland